(untitled) (Tempo e Argumento, 2022)
In this paper, we present the study of a transnational discursive community: the Inter-American Confederation of Continental Defence. This became the institutional meeting point for Latin American anti-communist intellectuals who, during the Cold War, articulated a conservative and counterrevolutionary nucleus of power. In the framework of the Cold War, this discursive community placed communism outside of humanity, and only contemplated its extermination. Thus, we analyse the discursive materiality that gradually colonized the state structures and gave rise to a systematic persecution against the communists and all those who, from the spheres of power, were typified as a threat. We structure the text in a chronological account that allows us to know the evolution of the Inter-American Confederation of Continental Defence, from its origins to its last continental congress. We use a wide documentary corpus (correspondence, minutes, bulletins, manuscripts, notes and speeches) compiled in Argentina, Mexico, Spain and the USA. Keywords: anti-comunist; discursive community; intellectuality; Latin America